Islamic culture and pre-Islamic beliefs in Central Asia - Dragnea, Mihai; Dragnea, Dorina; Marcos, Antonio Alonso (Lexington Books, 2024)
This volume contributes to a better understanding of the religious life in Central Asia as well as political and social issues in the region, with a focus on Islamic culture, traditions, and pre-Islamic beliefs.